THE EFFECT OF DISCOUNT AND SHOPPING LIFE STYLE ON IMPULSE BUYING WITH POSITIVE EMOTION AS AN INTERVENING VARIABLE ON THE SHOPEE SHOPPING PLATFORM - Sandra, Jelita Virliana; Karnawati, Tin Agustina; Bukhori, Mohammad (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2024)
Business that employs an online store using Shopee platform is Ghealsy.id. The aim of this study is to ascertain: (1) whether Discounts have an influence on Impulse buying, (2) whether Shopping lifestyle has an influence on Impulse buying, (3) whether Positive emotions have an influence on Impulse buying, (4) whether Discounts have an influence on Positive emotions, (5) whether Shopping lifestyle has a positive influence on Positive emotions, (6) whether Discounts have an influence on Impulse buying through Positive emotions as an Intervening Variable, and (7) whether Shopping lifestyle has an influence on Impulse buying through Positive emotions as an Intervening Variable. This study employs a quantitative (numeric) approach with 100 respondents as its sample. The results of this research demonstrate that: (1) Discounts have an effect on Impulse buying, (2) Shopping lifestyle does not have an effect on Impulse buying, (3) Positive emotions have an effect on Impulse buying, (4) Discounts have an effect on Positive emotions, (5) Shopping lifestyle has a positive effect on Positive emotions, (6) Through Positive emotions as an Intervening Variable, Discounts have an effect on Impulse buying, and (7) Through Positive emotions as an Intervening Variable, Shopping lifestyle has an effect on Impulse buying